2017
DOI: 10.1158/1538-7445.am2017-ct109
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT109: HITM-SIR: Phase Ib trial of CAR-T hepatic artery infusions and selective internal radiation therapy for liver metastases

Abstract: OBJECTIVES: There are no effective treatment options for patients with unresectable CEA+ liver metastases (LM) from gastrointestinal adenocarcinoma refractory to conventional systemic therapy. In the previous Hepatic Immunotherapy for Metastases (HITM) phase I study we demonstrated the safety and biologic activity of anti-CEA CAR-T cell hepatic artery infusions (HAI). HITM-SIR was a single arm phase Ib trial testing anti-CEA CAR-T HAI followed by selective internal radiation therapy (SIRT) in patients with ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These results were promising for enhancing the cytotoxic activity of CAR T cells, specifically for tumor cells, while sparing off-tumor normal tissue targets. Early studies have also demonstrated the feasibility of improving local drug delivery to metastases through hepatic artery infusion of targeted CAR T cells [ 116 ]. Improving immunotherapy efficacy by combing T-cell therapies with novel immune-enhancing agents such as ICI, T-reg-depleting therapies, costimulatory molecules like rimiducid, peroxisome proliferator-activated receptor gamma ligands, tyrosine kinase inhibitors, and other drugs that regulate inflammation may also be worth further investigation [ 117 , 118 , 119 , 120 , 121 ].…”
Section: Adoptive Cellular Therapymentioning
confidence: 99%
“…These results were promising for enhancing the cytotoxic activity of CAR T cells, specifically for tumor cells, while sparing off-tumor normal tissue targets. Early studies have also demonstrated the feasibility of improving local drug delivery to metastases through hepatic artery infusion of targeted CAR T cells [ 116 ]. Improving immunotherapy efficacy by combing T-cell therapies with novel immune-enhancing agents such as ICI, T-reg-depleting therapies, costimulatory molecules like rimiducid, peroxisome proliferator-activated receptor gamma ligands, tyrosine kinase inhibitors, and other drugs that regulate inflammation may also be worth further investigation [ 117 , 118 , 119 , 120 , 121 ].…”
Section: Adoptive Cellular Therapymentioning
confidence: 99%
“…Sixteen clinical trials target several antigens at the same time [ 35 , 36 ], and two clinical trials do not disclose the targeted antigen ( Table 1 ). The top six targeted antigens that are expressed on solid tumors in many different organs are (1) EGFR [ 37 , 38 , 39 , 40 , 41 ] (14 different organs), (2) NKG2D-ligands [ 42 , 43 ] (11 different organs), (3) HER2 [ 12 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] (11 different organs), (4) B7-H3 (10 different organs), (5) MUC1 (9 different organs), and (6) CEA [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] (9 different organs) ( Table 1 ).…”
Section: Car-t Cell Clinical Trials Against Solid Tumors—organs Tmentioning
confidence: 99%
“…2 patients with no viable liver metastases by PET scan after treatment for up to 12 monthsMedian OS post-treatment was 8.3 months with a mean OS of 9.8 monthsNCT01373047HITMDelivered into the hepatic circulation + systemic IL-2Katz et al [127] n = 9. 1 SD, OS: 4.5 months with 1 patient still alive at 23 monthsNCT 02416466HITM-SIRHepatic artery infusions and yttrium-90 SIR-spheresResults presented at AACR 2017 [128] n = 6. 3 SD, median OS 6.9 months AACR American Association for Cancer Research, AFP α-fetoprotein, ASCO American Association of Clinical Oncology, CAR chimeric antigen receptor, CAR-T chimeric antigen receptor-T cell, CD cluster of differentiation, CEA carcinoembryonic antigen, CEA-CAM5 Carcinoembryonic antigen-related cell adhesion molecule 5, CMV cytomegalovirus, CR complete response, CyFlu non-myeloablative preconditioning chemotherapy composed of cyclophosphamide and fludarabine, EGFR epidermal growth factor receptor, EGFRvIII variant III of the epidermal growth factor receptor, ESMO European Society for Medical Oncology, GD2 disialoganglioside, GPC3 glypican 3, FOLFOX leucovorin [folinic acid], 5-fluorouracil, and oxaliplatin, FU follow-up, HCC hepatocellular carcinoma, HER2 human epidermal growth factor receptor 2, HLA human leukocyte antigen, HITM hepatic immunotherapy for metastases, HITM-SIR HITM with selective internal radiation therapy, HITM-SURE HITM with surefire infusion system, IL interleukin, IL-13Rα2 interleukin-13 receptor α2, IP intraperitoneal, IV intravenous, mCRC metastatic colorectal cancer, MR mixed response, MSKCC Memorial Sloan Kettering Cancer Center, MUC16 mucin 16, MyD88 myeloid differentiation primary response 88, OS overall survival, NKG2D natural killer group 2 member D, NSCLC non-small cell lung cancer, OR objective response, OVA ovarian cancer, PD-1 programmed death 1, PD-L1 programmed death-ligand 1, PET positron emission tomography, PFS progression-free survival, PR partial response, PSCA prostate stem cell antigen, ROR-1 receptor tyrosine kinase-like orphan receptor 1, scFv single-chain variable Fragment, SD stable disease, SITC Society for Immunotherapy of Cancer, Tcm central memory T cells, TCR T cell receptor, TME tumor microenvironment, TNBC triple-negative breast cancer…”
Section: Current Treatment Of Solid Tumors In the Clinicmentioning
confidence: 99%